Shoreline change analysis in Da Nang, Vietnam, using CoastSat: A framework for assessing algal bloom risk - Nguyen, Van An; Tran, Thanh Thuong; Trieu , Xuan Hoa (Hue University Journal of Science: Natural Science, 2025)
Coastal zones worldwide are under immense pressure from climate change and anthropogenic activities, resulting in significant shoreline dynamics. This study presents a 20-year analysis (2004–2024) of shoreline changes in Da Nang, Vietnam, using the automated open-source CoastSat library with Landsat and Sentinel-2 satellite imagery. The analysis reveals a pronounced erosional trend in the southern coastal zones, linked to rapid urban development, and mild accretion on the Son Tra Peninsula, attributed to natural processes. The primary contribution of this research is the reframing of these physical dynamics as indicators of ecological risk. Our analysis revealed shoreline retreat rates up to –6.5 m/year in the southern sections and accretion up to +4.2 m/year in the northern transects during 2004–2023. These findings suggest that development-driven erosion not only accelerates sediment redistribution but may also facilitate nutrient loading into nearshore waters. In addition, anthropogenically altered morphology, such as channel realignment and coastal construction, appears to create semi-enclosed and hydrodynamically stagnant zones. These zones, in turn, can serve as potential incubation areas for harmful algal blooms. The study therefore provides quantitative evidence that shoreline dynamics can be used as a spatial proxy for assessing ecological risks in rapidly urbanising coasts.